AcBBX5, a B-box transcription factor from pineapple, regulates flowering time and floral organ development in plants - Ouyang, Yanwei; Zhang, Xiumei; Wei, Yongzan; He, Yukun; Zhang, Xiaohan; Li, Ziqiong; Wang, Can; Zhang, Hongna (Frontiers in Plant Science, 2022)
Flowering is an important factor to ensure the success of plant reproduction, and reasonable flowering time is crucial to the crop yield. BBX transcription factors can regulate several growth and development processes. However, there is little research on whether BBX is involved in flower formation and floral organ development of pineapple. In this study, AcBBX5, a BBX family gene with two conserved B-box domains, was identified from pineapple. Subcellular localization analysis showed that AcBBX5 was located in the nucleus. Transactivation analysis indicated that AcBBX5 had no significant toxic effects on the yeast system and presented transcriptional activation activity in yeast. Overexpression of AcBBX5 delayed flowering time and enlarged flower morphology in Arabidopsis. Meanwhile, the expression levels of AtFT, AtSOC1, AtFUL and AtSEP3 were decreased, and the transcription levels of AtFLC and AtSVP were increased in AcBBX5-overexpressing Arabidopsis, which might lead to delayed flowering of transgenic plants. Furthermore, transcriptome data and QRT-PCR results showed that AcBBX5 was expressed in all floral organs, with the high expression levels in stamens, ovaries and petals. Yeast one-hybrid and dual luciferase assay results showed that AcBBX5 bound to AcFT promoter and inhibited AcFT gene expression. In conclusion, AcBBX5 was involved in flower bud differentiation and floral organ development, which provides an important reference for studying the functions of BBX and the molecular regulation of flower.